Descriptions of the male and female of Stenopsyche siamensis Martynov, 1931, with observations on its relationship (Trichoptera: Stenopsychidae) - Ismail, A.R.; Edington, J.M.; Flint, O.S. (Taylor & Francis, 1993)
Both sexes of Stenopsyche siamensis are fully described and figured on the basis of new material collected in Peninsula Malaysia. The short terminal segment of the maxillary palpus, small eyes, and lack of tibial spurs on the foreleg, set this species apart from most of its congeners.